Exploratory laparotomy in chronic non-specific pain abdomen in lieu of therapeutic and diagnostic aspect: a prospective non randomized trial on 40 patients - Kochar, Mahinder Pal; Singh, Satyendra Pal (International Surgery Journal, 2020)
Background: A significant number of patients attending surgical or medical out doors and clinics of prominent doctors, we find them having thick record files visiting from one doctor to another. Majority of such patients diagnosis remain “chronic pain abdomen” in spite of all possible investigations and all sort of recent and ancient medicines. Aim of this study is to analyze the diagnosis and therapeutic value of exploratory laparotomy. Methods: A prospective non randomized study was done on 40 patients who follows our strict criteria and in spite of all relevant investigations’ diagnosis remain chronic nonspecific pain abdomen (CNSPA). Exploratory laparotomy was done and findings were recorded and analyzed to see its diagnostic and therapeutic value. Results: Patients of appendicular (maximum 27.5%) and tubercular disease present within one year of first appearance of pain whereas those having bands and adhesions after two years. Overall exploratory laparotomy was diagnostic and therapeutic in 80% patients. Conclusions: In selected patients of CNSPA exploratory laparotomy is therapeutic in 87.5% and diagnostic in 92.5% patients.